A new and unusual LBV-like outburst from a Wolf–Rayet star in the outskirts of M33. Issue 4 (14th January 2020) - Smith, Nathan; E Andrews, Jennifer; Moe, Maxwell; Milne, Peter; Bilinski, Christopher; Kilpatrick, Charles D; Fong, Wen-Fai; Badenes, Carles; Filippenko, Alexei V; Kasliwal, Mansi; Silverman, Jeffrey M
ABSTRACT: MCA-1B (also called UIT003) is a luminous hot star in the western outskirts of M33, classified over 20 yr ago with a spectral type of Ofpe/WN9 and identified then as a candidate luminous blue variable (LBV). Palomar Transient Factory data reveal that this star brightened in 2010, with a light curve resembling that of the classic LBV star AF And in M31. Other Ofpe/WN9 stars have erupted as LBVs, but MCA-1B was unusual because it remained hot. It showed a WN-type spectrum throughout its eruption, whereas LBVs usually get much cooler. MCA-1B showed an almost four-fold increase in bolometric luminosity and a doubling of its radius, but its temperature stayed ≳29 kK. As it faded, it shifted to even hotter temperatures, exhibiting a WN7/WN8-type spectrum, and doubling its wind speed. MCA-1B is reminiscent of some supernova impostors, and its location resembles the isolated environment of SN 2009ip. It is most similar to HD 5980 (in the Small Magellanic Cloud) and GR 290 (also in M33). Whereas these two LBVs exhibited B-type spectra in eruption, MCA-1B is the first clear case where a Wolf–Rayet (WR) spectrum persisted at all times. Together, MCA-1B, HD 5980, and GR 290 constitute a class of WN-type LBVs, distinct from S Doradus LBVs. They are most interesting in the context of LBVs at low metallicity, a possible post-LBV/WR transition in binaries, and as likely Type Ibn supernova progenitors.